IMPLEMENTASI EXPERT SYSTEM UNTUK MENGETAHUI PENYAKIT HIV AIDS MENGGUNAKAN ALGORITMA BEST-FIRST SEARCH (Infotekmesin, 2019)
According to UNAIDS until 2018, there are around 690 thousand people with HIV in Indonesia. Until now HIV is a virus that is slow to diagnose, but there are ways that can be used to diagnose the HIV virus. One way to find out whether someone is infected or not is by taking HIV test accompanied by counseling in the clinic (Voluntary HIV Counseling and Testing). Prospective patients feel ashamed during the initial diagnosis of a health examination. To solve these problems, it is necessary to build a system capable to diagnose HIV / AIDS using the best first search algorithm. The result of this study is to be able to facilitate patients checking their health by computerization easily, quickly and precisely, especially about HIV AIDS. Based on the system evaluation of the respondents, RK test results are obtained from the convenient use of the HIV expert system application that has a value of 3.72 with the title of satisfaction. the RK test results from the benefits of using the HIV expert system application has a value of 3.96 with the title of satisfaction.